Covering the muslim world : "fair and balanced" or Islamophobic? an examination of Fox News Channel (FNC) and International Crisis Group (ICG) - Roknifard, Iuliia (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research seeks to examine if there are signs of Islamophobia in the works of two large entities – the media called Fox News Channel (FNC) and the think-tank called International Crisis Group (ICG). Both started to operate around the same time, 1996 and 1995, respectively and accumulated vast experience in what they do. Islamophobia is an exaggerated fear, hatred, and hostility towards Islam and Muslims that is perpetuated by negative stereotypes resulting in bias, discrimination, and the marginalization and exclusion of Muslims from social, political, and civic life. This was officially declared a problem by the United Nations Alliance of Civilizations in 2011, while the League of Arab States has identified Islamophobia as an important area of concern. In this research, it was contraposed to the neutral scholarly, professional approach according to the tradition of professional scholarship applied by Western scholars to studies of the Muslim world. The data analyzed were selected primarily from FNC website (articles and TV programmes), ICG (reports, articles) and other related websites, and chronologically framed for 2011–2013. In 2011, the Syrian problems started to escalate into protests and later on into the civil war, while ethnic tensions in Myanmar received new development with a series of massacres in different locations and rising wave of anti-Muslim violence. In 2013, both conflicts reached a 'hot phase', but the approach of the two agencies in question to the issues of Syria and Myanmar was different since different geopolitical interests were at stake for each of them. The research found that although there are vivid signs of Islamophobia in the work of FNC when it concerns a wide range of issues, from Tahrir square events in Egypt until domestic matters in the USA, in the case of Syria, both FNC and ICG demonstrates rather Orientalist approach in its negative sense based on the continuously promoted need for the Western governments to intervene or make any decision with regards to the events happening in the two Asian countries. Thus, sometimes distortion or selective choice of facts served to the Orientalist purpose as set by Edward Said – to control and manage the Orient. ICG reports may serve as a useful source of information if read with a certain extent of criticism. As for FNC, since it has turned to be an absolute antipode of its motto 'Fair & Balanced' and to put forward opinions instead of facts, it is not recommended to be watched unless for a purpose of media study. The results do not fully confirm the hypothesis, but to modify it as the methods of covering the events were thoroughly investigated in the process. Their target audience and style of broadcasting ideas and findings are different, but the urge to create condition where the Orient can be better managed by the Occident is similar for both of them, while expressed in a differing manner.